Correlation between Chlorpyrifos Residues and Calcium Levels in Milk from Dairy Farms in Nakuru County, Kenya - Asamba, M. N.; Oshule, P. S.; Essuman, S.; Atego, N.; Chimbevo, L.; Nderitu, J. H.; Mapesa, J. (Africa Environmental Review Journal, 2022)
The use of organophosphate (OP) pesticides in dairy farming has increased due to their availability in the market and low prices. Chlorpyrifos (0, 0 – diethyl 0 - (3, 5, 6 – trichloro – 2 - pyridyl phosphonothioate; CP) is a medium-risk acaricide for humans whose widespread use in agriculture creates various health concerns. In dairy farms, extensive use of CP causes milk contamination and alteration of the composition and chemistry of dairy products. Few studies have examined the impact of CP residues on calcium levels in milk. Therefore, the present study aimed to determine the effect of Chlorpyrifos organophosphate on calcium levels in milk. Fresh milk samples were obtained from 15 Nakuru County, Kenya, dairy farms. HPLC was used to detect and measure CP levels in the milk samples, while calcium concentration was assessed through UV-VIS Spectrophotometry. The results show that approximately 53% of raw milk samples had significant detectable chlorpyrifos levels. All the positive milk samples exceeded the maximum residue limit (MRL). Calcium concentrations in the sampled milk from Nakuru County were not significantly higher or lower than the reference levels. A weak and negative correlation was found between calcium concentration and Chlorpyrifos residue levels (r = -0.2). These findings suggest that milk contamination with organophosphates affects their composition. Therefore, there is a need to properly handle milk to avoid contamination by chlorpyrifos and other pesticides used in agriculture. Besides, milk should be appropriately processed to reduce pesticide residues and metabolites in the final products.